Implicit Mentalizing Persists beyond Early Childhood and Is Profoundly Impaired in Children with Autism Spectrum Condition - Schuwerk, Tobias; Jarvers, Irina; Vuori, Maria; Sodian, Beate (Frontiers in Psychology, 2016)
Implicit mentalizing, a fast, unconscious and rigid way of processing other's mental states has recently received much interest in typical social cognitive development in early childhood and in adults with autism spectrum conditions (ASC). This research suggests that already infants implicitly mentalize, and that adults with ASC have a sustained implicit mentalizing deficit. Yet, we have only sparse empirical evidence on implicit mentalizing beyond early childhood, and deviations thereof in children with ASC. Here, we administered an implicit mentalizing eye tracking task to assess the sensitivity to false beliefs to a group of 8-year-old children with and without ASC, matched for chronological age, verbal and nonverbal IQ. As previous research suggested that presenting outcomes of belief-based actions leads to fast learning from experience and false belief-congruent looking behavior in adults with ASC, we were also interested in whether already children with ASC learn from such information. Our results provide support for a persistent implicit mentalizing ability in neurotypical development beyond early childhood. Further, they confirmed an implicit mentalizing deficit in children with ASC, even when they are closely matched to controls for explicit mentalizing skills. In contrast to previous findings with adults, no experience-based modulation of anticipatory looking was observed. It seems that children with ASC have not yet developed compensatory general purpose learning mechanisms. The observed intact explicit, but impaired implicit mentalizing in ASC, and correlation patterns between mentalizing tasks and executive function tasks, are in line with theories on two dissociable mentalizing systems.